2010
DOI: 10.1136/vr.c4119
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for seropositivity to bovine coronavirus and bovine respiratory syncytial virus in dairy herds

Abstract: A cross-sectional study was conducted to evaluate the association between herd-level characteristics, management routines and farm-level antibody status of bovine coronavirus (BCV) and bovine respiratory syncytial virus (BRSV) in 257 Swedish dairy herds. The possible spatial clustering of positive herds compared with negative herds was also investigated. For each herd, a pooled milk sample from five primiparous cows was analysed for the presence of antibodies to BCV and BRSV. Herd-level information was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 21 publications
8
48
2
3
Order By: Relevance
“…Thus the present study agreed with Yesilbag and Gungor (2008) who also recorded significant difference in serological prevalence of BHV-1 in large capacity farm containing >50 animals. The present result corroborate to the results of earlier studies where herd density was taken into account for potential raise for BRSV and PIV3 (SolisCalderon et al, 2007;Valarchar and Taylor 2007;Ohlson et al, 2010 andSaa et al, 2012). Management factors could also affect serological status and immunity of cattle.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus the present study agreed with Yesilbag and Gungor (2008) who also recorded significant difference in serological prevalence of BHV-1 in large capacity farm containing >50 animals. The present result corroborate to the results of earlier studies where herd density was taken into account for potential raise for BRSV and PIV3 (SolisCalderon et al, 2007;Valarchar and Taylor 2007;Ohlson et al, 2010 andSaa et al, 2012). Management factors could also affect serological status and immunity of cattle.…”
Section: Resultssupporting
confidence: 91%
“…Others are weaning prior to sale, crowding and introduction of new animals into a herd. Also, poor housing conditions have an important effect on BRD (Sanderson et al, 2008;Ohlson et al, 2010 andTaylor et al, 2010). How and to what extent these factors contribute to the disease is widely debated (Taylor et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A 100% prevalence of antibodies was demonstrated in a nationwide bulk tank milk survey in England and Wales [20], and 41-89% prevalence was found in Sweden [21], with higher prevalence in the southern parts where the cattle density is high compared to northern Sweden [22][23][24][25]. A high herd prevalence of BRSV was also reported in Danish dairy herds [26], and the infection is regarded as one of the most important welfare and economic problems in the Danish beef industry, associated with a high mortality among calves and a high rate of antibiotic treatment [27].…”
Section: Introductionmentioning
confidence: 99%
“…A high herd prevalence of BRSV was also reported in Danish dairy herds [26], and the infection is regarded as one of the most important welfare and economic problems in the Danish beef industry, associated with a high mortality among calves and a high rate of antibiotic treatment [27]. Studies have shown that there are negative effects associated with BRSV infections on herd health and animal performance [22,28] and an association between a high biosecurity level and lower herd prevalence [23]. There is, however, limited information about similarity and evolutionary relationship among the BRSV strains in the Swedish cattle population.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is usually found to be high (Elvander 1996, Paton and others 1998, Uttenthal and others 2000, Gulliksen and others 2009, Ohlson and others 2010). Such screenings have some disadvantages; animals will remain seropositive for several years after an infection.…”
Section: Introductionmentioning
confidence: 99%